Disentangling the photochemistry of benzocyclobutenedione. Issue 22 (25th May 2018) - Ma, Xiaonan; Wenzel, Michael; Schmitt, Hans-Christian; Flock, Marco; Reusch, Engelbert; Mitrić, Roland; Fischer, Ingo; Brixner, Tobias
Abstract : We combine transient absorption spectroscopy, quantum chemistry, and molecular dynamics to reveal multiple parallel and sequential channels of benzocyclobutenedione photochemistry. Abstract : The ultrafast photophysics and photochemistry of benzocyclobutenedione (BCBD) dissolved in dichloromethane is investigated by transient absorption spectroscopy in both the IR and the UV/Vis regime. The molecule is excited at 300 nm to the S3 (ππ*) state and a time scale from roughly 100 fs to several nanoseconds is covered. The initially excited S3 deactivates quickly to the lower-lying S1 (nπ*) state. Three parallel photochemical reaction pathways starting in the S1 state that compete with deactivation to S0 are identified in the transient IR spectra, two of them consisting of a sequence of steps. DFT/TDDFT calculations of the normal modes of the reactant and various photoproducts support the analysis of the transient spectra. The rapid internal conversion (IC) to the S1 state of BCBD is followed by a sub-picosecond vibrational relaxation (VR) to S1 ( ν = 0). In parallel BCBD loses one carbonyl group and forms benzocyclopropenone, which subsequently rearranges to cyclopentadienylidene ketene. Ring opening in the S1 ( ν = 0) state produces vibrationally hot bisketene, which cools within 22 ps. This reaction competes with the intramolecular rearrangement to singlet oxacarbene, which subsequently converts into the triplet carbene via intersystem crossing (ISC). The late-time product identified in the transient UV/Vis spectra is probably due to dimerization of the carbene. Molecular dynamics (MD) simulations of the early-time photochemistry of BCBD successfully reproduce the formation of the three main photoproducts.